2019
DOI: 10.1016/j.cej.2018.08.111
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel Production Using Thermochemical Conversion of Heavy Metal-Contaminated Biomass (HMCB) Harvested from Phytoextraction Process

Abstract: Over the past few decades, bioenergy production from heavy metalcontaminated biomass (HMCB) has been drawing increasing attention from scientists in diverse disciplines and countries owing to their potential roles in addressing both energy crisis and environmental challenges. In this review, bioenergy recovery from HMCBs, i.e. contaminated plants and energy crops, using thermochemical processes (pyrolysis, gasification, combustion, and liquefaction) has been scrutinized. Furthermore, the necessity of the imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 308 publications
(562 reference statements)
0
76
0
Order By: Relevance
“…The phytoremediation potential of castor bean plant is of primary importance, given the increasing number of PTE-contaminated soils. According to Dastyar et al [15], one-third of world resources are contaminated, mainly by heavy metals, although the real rate could be higher.…”
Section: Phytoremediation Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The phytoremediation potential of castor bean plant is of primary importance, given the increasing number of PTE-contaminated soils. According to Dastyar et al [15], one-third of world resources are contaminated, mainly by heavy metals, although the real rate could be higher.…”
Section: Phytoremediation Potentialmentioning
confidence: 99%
“…Pyrolysis greatly reduces the weight and volume of the biomass, resulting in easier disposal, while concentrating the PTEs in the char/ash fraction, which can eventually undergo additional treatments or metal extraction before discarding [14]. The most contaminated plant part or the metal-enriched slags generated from energy conversion can be removed according to the safe disposal of heavy metals [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that released metal ions such as nickel, zinc, copper and lead presented remarkable impact on the HTL reactions and could improve the bio-oil yield and promote product quality. 19,21,22 2.2 HTL procedure and analysis methods A schematic diagram of the experimental setup and procedure for the separation of the HTL products was shown in Fig. 1.…”
Section: Biomass Feedstockmentioning
confidence: 99%
“…Phytoextraction is one of the key processes of phytoremediation that involves the use of metal-accumulating plants (hyperaccumulators) to remove metals from soil © 2020 The Authors. Agronomy Journal © 2020 American Society of Agronomy by concentrating them in harvestable shoots and leaves (Dastyar, Raheem, He, & Zhao, 2019). Phytoextraction is an environmentally friendly and cost-effective method in comparison with physical and chemical methods, which have become some of the main methods of contaminated soil remediation.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of high quantities of Cd in soil endangers human health when it migrates up the food chain from the soil to plants, and Cd can be quickly absorbed by plants and transported to the leaves, resulting in toxicity (Dong, Fei, Wang, Hu, & Wang, 2019; Fusconi et al., 2006). Phytoextraction is one of the key processes of phytoremediation that involves the use of metal‐accumulating plants (hyperaccumulators) to remove metals from soil by concentrating them in harvestable shoots and leaves (Dastyar, Raheem, He, & Zhao, 2019). Phytoextraction is an environmentally friendly and cost‐effective method in comparison with physical and chemical methods, which have become some of the main methods of contaminated soil remediation.…”
Section: Introductionmentioning
confidence: 99%